Full-field deformation evolution characteristics of freeze-thawed fault zone rock mass revealed by digital image correlation: a lab-scale investigation - Yihai Zhang; Yihai Zhang; Beibei Sun; Beibei Sun; Yi Ren; Yi Ren (Frontiers in Materials)
This work aims to reveal the macro-meso fracture evolution responses of fault zone samples subjected to repeated freeze-thaw (FT) weathering utilizing digital image correlation technology (DIC). Remolded specimens were prepared and then subjection to FT cycles of 0, 20, 40, and 60, respectively. Testing results show that the degradation effect of freeze-thaw on the uniaxial compressive strength of the fault fracture zone rock masses is significant, with peak strengths deteriorating by 20.2%, 32.7%, and 45.2% for specimens subjected to 20, 40, and 60 cycles, respectively, compared to specimens without FT treatment. Due to the elastic mismatch between the fine-grained matrix and the rock blocks within the fault fracture zone, the strain and displacement fields during loading exhibit pronounced heterogeneous characteristics. It is shown that freeze-thaw treatment leads to increasingly complex failure modes, with the fracture patterns transitioning from tensile failure to conjugate shear failure as the number of FT cycle increases. It is suggested that the impact of freeze-thaw on the internal components of the fault fracture zone rock masses varies considerably, with frost heave forces readily developing at rock-soil interfaces, pores, and microcracks, resulting in damage propagation, and ultimately diminishing the rock mass’s resistance to deformation.